AKULTURASI ETNIS INDIA DI MINANGKABAU: IDENTITAS BUDAYA DAN INTERAKSI SOSIAL - Iftita Rahmi Efendi; Yuliana Yuliana; Agusti Efi; Elida Elida (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2026)
This research conducted in Kampung Keling, Padang City, West Sumatra Province aims to explore the dynamics of the existence of the Indian ethnic community within the Minangkabau cultural environment as a representation of Indonesia's ethnic diversity. The main objective of the study is to understand how social interactions between the Indian ethnic group and the Minangkabau community influence cultural identity, the preservation of customs and traditions, religious practices, and socio-economic development among the Indian community. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that the Indian ethnic group in the Minangkabau region has experienced a gradual acculturation process, resulting in a form of cultural transformation that blends elements of Indian heritage with Minangkabau culture. Over time, they have successfully adapted to the local social environment while still maintaining distinctive cultural characteristics rooted in their ancestral traditions. Social interaction between the two ethnic groups plays a significant role in shaping processes of adaptation and cultural acculturation. The commitment to preserving Indian cultural identity is reflected in efforts to sustain traditional customs, religious values, and cultural practices, despite the pressures of modernization and globalization. Various cultural activities and community organizations help support this continuity. Overall, this research provides deeper insight into cultural plurality in Indonesia and highlights the importance of multicultural harmony. It offers valuable reference material for policy development related to ethnic diversity and cultural identity preservation within multicultural societies.